Analysis of the indirect correlation between academic achievement, intrinsic and extrinsic motivation, and self-efficacy on teaching readiness - Andi Maga Umara; Pardjono Pardjono; Galeh Nur Indriatno Putra Pratama (Jurnal Pendidikan Vokasi, 2024)
This research aims to determine the indirect correlation between academic achievement, intrinsic motivation, extrinsic motivation, and self-efficacy on the teaching readiness of education study program students. This type of research is quantitative and inferential in testing the hypothesis. This research was conducted in October 2022, and the subjects in this study were 167 students from the Universitas Negeri Gorontalo classes of 2018 and 2019. The sampling technique used is saturated sampling, which is used to select samples that include every member of the population. The instrument used in this research is a questionnaire that has been validated by experts and has been tested for validity and reliability.  The results of the research show that (1) There is an indirect positive influence between academic achievement on teaching readiness through self-efficacy by 20.9%, intrinsic motivation on teaching readiness through self-efficacy by 74.1%, and extrinsic motivation on teaching readiness through self-efficacy by 43.3%; (2) There is a direct positive influence between self-efficacy on teaching readiness by 42.9%. Thus, self-efficacy is directly related to teaching readiness and can mediate the relationship between academic achievement, intrinsic and extrinsic motivation, and teaching readiness. The findings of this research can be used to develop and evaluate engineering education study programs that will prepare graduates to become teachers.